P31 Long-term albumin administration improves survival, reduces TLR4 mediated hepatic inflammation and reduces gut translocation in models of cirrhosis. (20th September 2022) - Phillips, Alexandra; Zhao, Qianwen; Habtesion, Abeba; Andreola, Fausto; Davies, Nathan; Edwards, Lindsey; Macnaughtan, Jane; Jalan, Rajiv
Abstract : Introduction: Long-term albumin administration reduces mortality in patients with decompensated cirrhosis, however, underlying mechanisms are unknown. The aims of this study were to investigate how the absence of endogenous albumin and albumin administration impacts liver injury, toll-like receptor 4 (TLR4) signalling and gut translocation. Methods: 10 rodent groups: Naïve, cirrhosis (4-wk; bile-duct ligation (BDL)) and acute-on-chronic liver failure (ACLF) models (induced by lipopolysaccharide (LPS) 0.025 mg/kg intraperitoneal (i.p.) to BDL) ± albumin infusion (1.5 g/kg ip; 2-wk) of analbuminaemic (NAR) and wild-type (SD) rats. Plasma biochemistry and hepatic TUNEL staining. Hepatic TLR4 expression (hTLR4): qPCR of TLR4. TLR4 transactivation: TLR4 reporter cell assay of plasma. Cell death: plasma cell death ELISA. Gut permeability: d-lactate in plasma. Ileal integrity: western blot of tight junction proteins. Results: ALT levels significantly improved after albumin administration in SD BDL LPS group (p=0.01), and non-significant improvement in SD BDL and NAR BDL LPS. Significant reduction in the liver of TUNEL positive areas in SD BDL LPS and NAR BDL groups with albumin administration (p<0.05). Coma-free survival increased from 62.5% to 80% between NAR and SD animals exposed to LPS respectively, with 100% survival in NAR animals exposed to LPS after albumin administration. hTLR4: NAR animals had greater hTLR4 expression, with a significant reduction of hTLR4 expression after albumin administration in all groups (p<0.05). TLR4 transactivation: All treatment groups had a reduction in plasma LPS with albumin administration, with significance in NAR BDL LPS with albumin administration (p<0.001). Cell death: All treatment groups had a reduction in circulating markers of cell death in those treated with albumin. Markers of gut permeability: Plasma D-lactate showed a reduction in all treatment groups with albumin (see figure 1 ). Tight junction: ZO-1, claudin-4 and occludin in ileum showed a reduction in NAR diseased animals compared to SD groups with albumin administration increasing tight junction protein abundance in all disease groups. Conclusions: These novel findings show analbuminaemic animals have increased mortality, significantly increased liver injury, increased gut translocation and sensitivity to LPS. Chronic albumin administration partially reversed this, resulting in decreased TLR4 pathway activation and improved gut integrity. The data provide mechanistic insight into the biological effect on albumin on gut-liver interactions.